Hubungan Saluran Komunikasi dengan Persepsi tentang Inovasi Teknologi Geomembrane pada Produksi Garam di Kabupaten Sumenep - Ach. Haris Abdi Manaf; Djuara P. Lubis; Istiqlaliyah Muflikhati (Institut Pertanian Bogor, 2022)
The communication channel is a media for sustainable agricultural development and the use of innovation and technology for improving people's welfare without ignoring the preservation of natural and environmental resources. The government encourages the application of geomembrane technological innovations in salt production with the aim of increasing the productivity and quality of the salt produced. The purpose of this reseach is to describe the communication channels and perceptions of people's salt farmers on geomembrane technology innovation, and analyze the correlation of communication channels with perceptions of salt pond technology innovation. The unit of analysis is community salt farmers in the Gersik Putih village and Sentol Daya village, Sumenep Regency, with 68 respondents. Data were analyzed using Pearson correlation method. The result of the research showed that the bottom of the salt salt farmer uses all communication channels except internet hybrid media. The lowest perception is the level of complexity and the highest perception is the level of trialability in geomembrane technology. Interpersonal communication channel related to perceptions of innovation on the characteristics of the level of relative advantage, level of compatibility, and level of observability. While group communication netagative relates to the level of trialability.